2020
DOI: 10.1039/c9nr08574b
|View full text |Cite
|
Sign up to set email alerts
|

Large amplitude charge noise and random telegraph fluctuations in room-temperature graphene single-electron transistors

Abstract: We analyze the noise in room-temperature liquid-gated quantum dots. We demonstrate large amplitude charge noise and two-level fluctuations in the current level which we attribute to charge trapping at the disordered graphene edges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 33 publications
(49 reference statements)
0
16
0
Order By: Relevance
“…Nanopores integrated with complementary nanostructures have received interest in recent years as they have the ability to overcome issues associated with ionic current based nanopore sensing including limited device density [59,60] and low bandwidths. [61][62][63] Such complementary nanostructures include field-effect sensors, [59,[64][65][66] tunneling nanogaps, [67,68] plasmonic nanostructures, [69,70] radiofrequency antennas, [62] and dielectrophoretic electrodes. [9] To date, the development of these devices has been limited by the difficult fabrication processes that are required to integrate pores with complementary nanostructures.…”
Section: Cbd With Microelectrodes On the Membrane Surfacementioning
confidence: 99%
“…Nanopores integrated with complementary nanostructures have received interest in recent years as they have the ability to overcome issues associated with ionic current based nanopore sensing including limited device density [59,60] and low bandwidths. [61][62][63] Such complementary nanostructures include field-effect sensors, [59,[64][65][66] tunneling nanogaps, [67,68] plasmonic nanostructures, [69,70] radiofrequency antennas, [62] and dielectrophoretic electrodes. [9] To date, the development of these devices has been limited by the difficult fabrication processes that are required to integrate pores with complementary nanostructures.…”
Section: Cbd With Microelectrodes On the Membrane Surfacementioning
confidence: 99%
“…Recently, Fried et al, investigated the noise characteristics of a graphene quantum dot at room temperature in liquid environments. 67 Unlike reported studies, 68 they observed that the noise was significantly independent of the liquid environment and the substrate. In this study, the noise was attributed to charge trapping and detrapping at the disordered graphene edges.…”
Section: Discussionmentioning
confidence: 70%
“…This may simplify the complex signal decovolution processes currently required to sequence DNA using biological nanopores where multiple bases reside within the pore at a given time. Graphene and MoS 2 can also be used as field-effect sensors 56,69,167,174 that when integrated with nanopores offer larger detection bandwidths and increased device densities compared to what is possible using ionic current measurements.…”
Section: Electrochemical Reactionmentioning
confidence: 99%